Pengendalian Mutu Alat Skir Katup Otomatis Menggunakan Peta Kendali dengan Metode Bootstrap - Yuvani Oksarianti; Dina Fitria (Journal of Mathematics UNP, 2022)
Compression leaks occur in valves caused by soot resulting from the combustion process of the combustion engine. To overcome valve leaks, it’s necessary to clean using an innovative tool called valve grinding automatic system. The purpose of this study was to determine the quality of this tool based on the control chart using the bootstrap method. Based on the research results, the control charts X ̅ dan R show that the cleaning process is in a controlled and stable state (in statistical control). The quality of the valve cleaning process using this tool is able of producing cleaning according to standard cleaning specifications.